The Role of Employee Empowerment in Strengthening Corporate Outcomes: A Qualitative Study - Jashwant, Sandeep (Integrated Journal for Research in Arts and Humanities, 2023)
Employee empowerment has become a pivotal strategy for organizations aiming to enhance their corporate outcomes in a competitive and dynamic business environment. Empowerment involves granting employees autonomy, access to resources, and opportunities for decision-making, which fosters accountability, innovation, and commitment. This study explores how employee empowerment influences organizational performance, focusing on both global and Indian perspectives. Using a qualitative approach, the research draws insights from interviews, case studies, and literature. It highlights the key factors enabling empowerment, challenges in implementation, and its impact on corporate productivity, innovation, and employee satisfaction. Case studies of Indian firms such as Tata Consultancy Services (TCS), Infosys, and Maruti Suzuki demonstrate practical applications and outcomes.